How did the deer cross the fence: An evaluation of wildlife-friendlier fence modifications to facilitate deer movement - MacDonald, Amanda M.; Jones, Paul F.; Hanlon, Jason A.; Martin, Brian H.; Jakes, Andrew F. (Frontiers in Conservation Science, 2022)
Fences are a common feature throughout the landscape of North America’s Great Plains region. Knowledge surrounding the harmful implication that fences have on the movement of wildlife, specifically ungulates, is expanding. Across the region, it is accepted that there is a need to mitigate the impacts of barbed wire fencing and that “wildlife-friendlier” fence designs are emerging as a practical tool to meet these goals. Here we evaluate the response of sympatric deer species to the implementation of two fence modifications, fastening the top two wires together using clips and the installation of polyvinyl chloride (PVC) pipe to encompass the top two wires. We also aim to determine the optimal top wire height to allow for successful crossing by deer, with the goal to provide a more robust understanding of effective wildlife-friendlier fence standards. We used remote trail cameras to capture crossing events and recorded responses for mule deer (Odocoileus hemionus) and white-tailed deer (Odocoileus virginianus). Using generalized linear mixed modelling, we tested the influence modifications had on crossing success and decisions prior to and after the modifications were installed compared to control sites. We found that these modifications had little impact on deer crossing behavior. We determined that wire height had the greatest impact on the permeability of fences, but that deer permeability was strongly influenced by species and sex. We found that the current maximum recommended top wire height of 102 cm (40 inches) is adequate to allow individuals of both deer species to cross over the fence, with the exception of female mule deer. Our results also indicate as the top wire height reaches 110 cm (43 inches) or higher, that the probability of successfully jumping over the fence dramatically drops off, with the exception for male mule deer. We recommend the installation of clips as a cost-effective method to lower top wire height and PVC pipe to improve fence visibility and potentially reduce entanglement events, all while effectively keeping livestock in intended pastures.